Time to Antibiotics and Clinical Outcomes in Pediatric Cancer Patients with Fever: Evaluating the "Golden Hour" Concept - Medalit Luna Vilchez; Grisell Leonor Portilla Uribe; Mitsi Lorraine Santiago Abal; Victoria Angélica Godoy Vila; Alicia Janeth Mafaldo Rengifo; Gloria Francia Oscanoa (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background In low- andmiddle-income countries, infections remain the leading cause of treatment-related mortality in pediatric patients with cancer. The "Golden Hour" concept advocates antibiotic administration within 60 minutes of emergency department (ED) triage to reduce sepsis and ICU admission. We evaluated whether time to antibiotic administration (TTA) >60 min versus ≤60 min impacts adverse clinical outcomes in children with cancer and fever. Methods We conducted a prospective longitudinal at the Instituto Nacional de Salud del Niño San Borja, a national pediatric referral center in Lima- Peru, from April 2024 to Octuber 2025. The study included all patients <18 years with an established cancer diagnosis and documented fever upon ED triage. TTA was defined as the Interval from ED traige to first antibiotic dose. Clinical outcomes assessed included documented infection, sepsis, hospitalization, ICU admission, and mortality. Comparative analyses used Fisher´s exact test and the Mann-Whitney U test. Results Among 162 febrile episodes in 122 patients, 84 (51.9%) achieved TTA ≤60 min. Median age was 5.5 years (IQR 4–8), 52.5% were male and acute lymphoblastic leukemia predominated (78.4%). The median neutrophil count was 1035 cells/μL (IQR: 138 – 5430). TTA ≤60 min (n=78) was linked to lower documented infection (51.2% vs. 87.2%; p<0.001) and higher ED temperature (median 38.0°C [37.5–38.4] vs. 37.5°C [IQR 36.6–38.0]; p=0.007). No differences were observed in sepsis (9.6%vs.3.9%; p=0.213), ICU transfer (1.2%vs.1.3%; p>0.999), hospitalization (79.5% vs.73.1%; p=0.359), or mortality (3.6%vs.2.6%; p>0.999). Delayed presentation (>3 h post-fever onset) occurred in 113 episodes (72.4%), driven primarily by pre-hospital antipyretics in the TTA >60 min group (81.3% vs. 71.9%; p=0.014). Conclusion Achievement of antibiotic administration ≤60 min of ED triage was associated with a lower rate of documented infections and higher presenting temperatures in the ED, likely reflecting effective clinical prioritization of more acutely ill patients. However, a TTA >60 min showed no association with increased risks of sepsis, ICU transfer, prolonged hospitalization, or death. These findings suggest that strict adherence to "Golden Hour" targets may not yield superior outcomes in low- and middle-income countries and underscore the need for a risk-stratified, patient-centered approach to antibiotic timing in pediatric oncology fever management.